Teori Al-Qur'an dalam Mengatasi Anak Tantrum dan Relevansinya dengan Love Languages - Najiyah, Wasilatun; Rifqatul Husna (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Tantrums in children are excessive reactions when they have difficulty in managing their emotions as indicated in QS. al-A'raf: 150 with the characteristics of great anger, hurling something at others, and pulling someone’s hair aggressively. In the Qur'an, there is the best solution for dealing with tantrums contained in QS. Al Baqarah: 156, QS. Ar Ra'd: 28, and QS. Taha: 44. Therefore, this study provides a new approach to overcoming tantrums in children by combining two concepts, namely the theory of the Qur'an in overcoming the child and love language in the Qur'an. This research is a thematic research that uses the library research method with data analysis techniques in the form of content analysis. The results of this study concluded that some verses that were relevant to the concept of Love Languages ​​namely QS. Al Qalam: 4, QS. Yusuf: 99, QS. Al Baqarah: 127, QS. An-Naml: 35-36, and QS. al-Ahqaf: 15 emphasize the importance of recognizing the language of love according to the tantrum. This concept aims so that the child's character can be formed properly so that it has a positive impact on its development. The combination of the Qur'an and Love Languages ​​in overcoming tantrums is not only a solution to the situation but also a form of implementation in caring for children who are mandated by Allah.